2010
DOI: 10.1007/s00268-010-0886-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Clinicopathologic Features of Papillary Thyroid Microcarcinoma Based on 7‐mm Tumor Size

Abstract: A PTMC≤7 mm is less likely to have aggressive features, including central lymph node metastasis, capsule invasion, extrathyroidal extension, and lymphovascular invasion, than a PTMC>7 mm. Because the aggressiveness of PTMC was found mainly in the patients with tumors >7 mm, we think that a cutoff value of 7 mm may be considered the threshold of aggressiveness of PTMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 32 publications
10
50
0
8
Order By: Relevance
“…The level of evidence for recommending prophylactic CCND by the American Thyroid Association (ATA) 2009 guidelines is considered insufficient; therefore, the issue still remains unresolved [12]. Numerous published studies have adopted a more aggressive treatment approach than that proposed in the guidelines of some scientific societies [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of evidence for recommending prophylactic CCND by the American Thyroid Association (ATA) 2009 guidelines is considered insufficient; therefore, the issue still remains unresolved [12]. Numerous published studies have adopted a more aggressive treatment approach than that proposed in the guidelines of some scientific societies [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the beneficial effects on one hand and supported arguments against prophylactic CCND on the other hand. A high proportion of autopsy findings and pathological specimens have shown metastasis in CCLN [14][15][16][17]. Although US has been regarded as a sensitive imaging modality for thyroid screening and diagnosis, US has a low sensitivity in evaluation of metastasis in CCLN [19].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been suggested that the selected cut-off size of 10 mm may be too arbitrary and can be further refined (59). There is a trend to use cut-off value of 7 mm as a reasonable threshold for aggressiveness in microPTC (60), although other groups have suggested cut-off values from 5 mm to 9 mm.…”
Section: :4mentioning
confidence: 99%
“…bei einem Tumordurchmesser nur wenig unter 10 mm in einem interdisziplinär abgestimmten Behandlungskonzept mit dem Patienten zu diskutieren. Argumente für eine Radiojodtherapie auch bei einem unifokalen, papillären Karzinom unter 10 mm ergeben sich aus den Studien von Machens et al [18] und Lee et al [11], die eine ansteigende Wahrscheinlichkeit lymphogener Mikrometastasen beim PTC ab einem Schwellenwert von 5 mm Tumordurchmesser gezeigt haben. Lee et al [11] empfahlen, die 131 I-Therapie ab einem Tumordurchmesser ≥7 mm durchzuführen.…”
Section: Ablation Als Indikationunclassified